Forgiveness, Religiousness, and Life Satisfaction: An Empirical Study on Turkish and Jordanian University Students - (:unkn) unknown (My University, 2016)
Affetme; sağlık, kişilik, bağlanma ve dindarlıkla ilişkilendirilerek başta din psikolojisi olmak üzere psikolojinin farklı alt dallarında incelenmiştir. Bu makalede affetme, dindarlık ve hayat memnuniyetiyle (yaşam doyumu) ilişkisi bağlamında araştırılmaktadır. Araştırmanın temel amacı dindarlığın hem affetme hem de hayat memnuniyeti üzerindeki rolünün belirlenmesi, aynı zamanda affetmenin hayat memnuniyeti üzerindeki rolünün tespitidir. Ayrıca araştırmada cinsiyet ve yaşın affetme eğilimindeki rolü ele alınmış, Ürdün ve Türkiye'den iki farklı örneklem seçilerek kültürel bir karşılaştırma da hedeflenmiştir. Araştırma örneklemi İstanbul ve İrbid'de okuyan üniversite öğrencilerinden oluşmaktadır. Araştırmaya katılanların 223'i (%75,6) kadın, 72'si (%24,4) erkektir. Katılımcıların yaşları, 17 ile 50 arasında değişmektedir. Yaş ortalaması ise 22'dir. Örnekleme, Affetme Eğilimi Ölçeği ve Hayat Memnuniyeti Ölçeği uygulanmıştır. Elde edilen bulgulara göre, affetme eğiliminin öç alma alt boyutunda cinsiyetin anlamlı bir farklılık oluşturduğu anlaşılmıştır

Forgiveness has been examined in the science of psychology and its sub-departments like psychology of religion with the focus on the interrelations between personality, attachment, health, religiosity, and so on. In this article, forgiveness has been investigated in the context of its relation with religiosity and life satisfaction. The main aim of the study is to delineate the role of religiosity on forgiveness and life satisfaction. Furthermore, the relationship between forgiveness and demographics (gender and age) and the effect of cultural differences on forgiveness have also been investigated in this study. A further goal of this paper will be to describe the effect of forgiveness on life satisfaction. In order to discern the abovementioned goals, the Interpersonal Forgiveness Scale and Life Satisfaction Scale were applied to a sample of 295 students from Yarmouk University in Irbid, Jordan, and Marmara University in Istanbul, Turkey. According to the findings, female students had higher means in “vengeance,” a sub-department of forgiveness, than male students. Female students were more likely to be satisfied with life than male students
Affetme, Dindarlık ve Hayat Memnuniyeti İlişkisi: Türk ve Ürdünlü Üniversite Öğrencileri Üzerine Bir Araştırma
Keywords: Psikoloji